The Effect of X-ray Radiation on Malondialdehyde Levels in Radiology Workers in Selected Hospitals in Indonesia - Y Denny Ardyanto W; Abdul Rohim Tualeka; Rizaldy Fathur Rachman; Tamilanban Thamaraikani; Velu Perumal; Ahsan Ahsan; Pudji Rahmawati; Suardi Zurimi; Salsabila Novianti (Poltekkes Kemenkes Surabaya, 2024)
The use of ionizing radiation in radiology units is essential for disease diagnosis. However, the energy of this radiation is sufficient to ionize the atoms and molecules in the substance it moves through, potentially posing health risks. This study aimed to analyze the effect of an effective dose of X-ray radiation on malondialdehyde (MDA) levels, a marker of oxidative stress, in radiographers. With an observational design, this study was conducted cross-sectionally at hospitals X and Y from January to April 2023, involving 19 radiographers exposed to X-ray radiation. MDA levels were measured using the Thio Barbituric Acid Reactive Substances (TBARS) method, and data were analyzed using SPSS, including descriptive, bivariate, and multivariate analyses. The results showed that all respondents had abnormal MDA levels, but the effective dose of radiation did not significantly affect MDA levels (p > 0.05). In contrast, working hours showed a significant influence on MDA levels, where an increase in working hours correlated with an increase in MDA levels. Thus, although the radiation dose received is considered safe, there is evidence of significant oxidative stress in radiographers, which requires further attention regarding the management of radiation exposure in the work environment.Ionizing radiation sources are used by the radiology unit for diagnosing diseases. When radiation contacts an element with sufficient energy, the atoms and molecules can become ionized. The research aims to examine how effective X-ray radiation doses affect malondialdehyde (MDA) levels. The methodology of this research is observational because no intervention is used—just the observation of the variables. In recognition of the type of data and analysis, the study is quantitative. While during the study, data from the dependent variable is only collected once, it is cross-sectional in design. Nineteen radiographers who deal directly with X-ray radiation exposure participated in the study, which took place in hospitals X and Y between January 2023 and April 2023. Based on the data shown in Table 3, every respondent has blood levels of malondialdehyde (MDA) that are abnormal. MDA levels are not impacted by the radiation's effective dose. More details about MDA and its connections to radiation exposure and oxidative stress can be found in the search results. All respondents show abnormally high levels of MDA in their blood; working hours have an impact on MDA levels; and effective radiation doses do not affect MDA levels. All radiation doses received have been considered safe.